Orientalism : a critical analysis of Muslim characters in Tamburlaine The Great and jewish characters in The Jew of Malta - Aini Fatimah binti Amat Kamal (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This qualitative research attempts to discover elements of Orientalism in Muslim and Jewish characters in two selected plays by Christopher Marlowe, namely Tamburlaine the Great and The Jew of Malta. This is achieved by finding and analysing elements of Orientalism found in Marlowe's plays using Edward Said's Manifest Orientalism framework in his book Orientalism. The study found elements of Orientalism in Marlowe's plays but there is limited evidence to substantiate Marlowe's influences in his playwriting. Even if there is evidence, the influence that may have led to Marlowe producing the plays may be his own personal experience with Jews during his lifetime. The analysis establishes that Marlowe's writings exhibit his personal biased views of Jewish and Muslim communities by stereotyping them, and his illustration on how the East is laden with natural resources and precious gems from his own imagination. Additionally, the study identifies apparent elements of stereotype, binary opposition of characters and manifestation of latent ideas that Marlowe perceived about the East in his plays. The analysis of the plays illustrates elements of Orientalism such as stereotyping Muslim and Jewish characters as well as emphasizing the binary opposition of Christianity's superiority to selfish and wealthy Jewish merchants and blood-thirsty Muslim conquerors. This concludes that Marlowe's plays Tamburlaine the Great and The Jew of Malta contains elements of Orientalism.